Analisis Hambatan Belajar (Learning Obstacle) pada Materi Statistika Siswa Kelas VI SDN 6 Palembang - Zalika Melati; Nyiayu Fahriza Fuadiah; Nora Surmilasari (Pentagon : Jurnal Matematika dan Ilmu Pengetahuan Alam, 2024)
In class VI.A students, there are still many students having difficulty in doing statistics problems. Therefore, this research needs to be done in order to find out the learning obstacles experienced by grade VI students of SDN 6 Palembang on statistics material. Learning obstacle is divided into three types, namely ontogenic obstacle, didactial obstacle, and epistemological obstacle. The research method used in this study is a descriptive qualitative method. The instruments used in this study consisted of learning obstacle diagnostic tests, interviews, material analysis, lesson plan analysis, and textbook analysis and students of grade VI.A SDN 6 Palembang as the subjects in this study who were respondents who carried out learning obstacle diagnostic tests and interviews. Learning obstacles can be found based on the results of the analysis of learning obstacle diagnostic tests, interviews with homeroom teachers and students of class VI.A, lesson plan analysis and textbook analysis. The results of this study found learning obstacles, namely ontogenic obstacles such as lack of interest in learning mathematics and lack of student activeness in learning, didactical obstacles such as learning resources that are still limited and epistemological obstacles, namely lack of understanding of statistical concepts.